Green Synthesis of Silver Nanoparticles Using Leaves Extract of Bauhinia Tomentosa Linn and its Invitro Anticancer Potential. (2015) - Mukundan, D.; Mohankumar, R.; Vasanthakumari, R.
Abstract: Nanotechnology can be applied to solve many problems in the field of telecommunications, biotechnology, microelectronics, textiles, energy, etc. The present investigation deals with the green synthesis of silver nanoparticles (AgNP) using Bauhinia tomentosa Linn (Kanchini) leaves extract and its invitro anticancer potential. Aqueous extract was reacted with 1 mM of Silver Nitrate (AgNO3 ) and the change in color from pale yellow to reddish brown indicated the reduction of Ag + ions to Ag 0 . The synthesized AgNP's were characterized using UV-Visible spectrophotometer, FTIR, FESEM-EDAX, HR-TEM and XRD. The scavenging effect was determined using DPPH with Ascorbic acid as standard. The in-vitro anticancer activity of the extract and AgNP's was confirmed by MTT assay on the cell lines of lung A-549 carcinoma cells.